Plasma-treated Ti3+-doped sodium titanate nanosheet arrays on titanium foil as a lithiophilic current collector for a stable lithium metal anode. Issue 46 (20th May 2019) - Zhang, Qi; Luan, Jingyi; Sun, Dan; Tang, Yougen; Wang, Haiyan
Abstract : Ar/H2 plasma-treated Ti 3+ -doped sodium titanate nanosheet arrays on titanium foil can induce a uniform lithium deposition. Abstract : Sodium titanate nanosheet arrays grown on titanium foil are utilized as a current collector for a lithium metal anode and Ti 3+ is introduced by Ar/H2 plasma for a uniform lithium deposition. The lithium nucleation overpotential and voltage hysteresis are dramatically reduced by increased active sites and improved electrical conductivity.